PENGARUH INTERPERSONAL COMMUNICATION DAN CORE VALUES AKHLAK TERHADAP PRESTASI KERJA KARYAWAN - Ginting, Agnes Monica Br.; Sihombing, Marlon (Peneliti.net, 2024)
This study aims to analyze the influence of Interpersonal Communication and Core Values AKHLAK on Employee Job Performance at Bank Tabungan Negara KC Medan. The form of research used in this research is quantitative research with an associative approach. The sample in this study amounted to 46 people, and the sampling techniques used were simple random sampling. Primary data in this study were obtained through questionnaires directly, while secondary data were obtained through literature studies. The data analysis methods used are instrument tests, classical assumption tests, multiple linear regression analyses, and hypothesis testing. The results showed that Interpersonal Communication and Core Values AKHLAK significantly affected both partially and simultaneously Employee Job Performance at Bank Tabungan Negara KC Medan. The determination coefficient test shows a close relationship between Interpersonal Communication and Core Values AKHLAK with an R-value of 0.606. Based on the Adjusted R Square value, it is also known that the Interpersonal Communication and Core Values AKHLAK variables contribute 33.8% to the entrepreneurial decision variable. At the same time, factors outside the capital of this study influence the rest.